Recent progresses and remaining issues on the ultrathin catalyst layer design strategy for high-performance proton exchange membrane fuel cell with further reduced Pt loadings: A review. (8th January 2022) - Deng, Xiang; Huang, Chao; Pei, Xiaodong; Hu, Bin; Zhou, Wei
Abstract: This study presents a detailed review on the ultrathin catalyst layer (UTCL) design strategy for high-performance proton exchange membrane fuel cell (PEMFC). Specifically, the motivation towards the further reduced Pt loadings by applying the UTCL electrode design is firstly introduced from both the historical and mechanism deductions. Then, the recent developments on the UTCL designs belonging to different classifications are summarized with their respective merits. In particular, the critical issues remained on these ultra-thin, low Pt-loaded electrodes are proposed with alternative solutions. Finally, the whole review is concluded with the perspectives on the possible future directions settling the remaining challenges. Highlights: Different kinds of ultrathin catalyst layer (UTCL) designs for PEMFCs are proposed with multiple advantages. The breakthroughs on the most critical issues for the possible commercialization of UTCL electrodes are highlighted. The current challenges and perspectives of UTCL design are summarized and discussed.